Education and employee skill-set certifications in the new economy: a it-related case study - Coelho, João (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Presently, any individual can claim to be an “expert” in a particular process, subject matter or technology. In fact, one disadvantage in the tacit knowledge approach is that individuals in an organization may claim to have knowledge that they do not actually have or may claim to be more knowledgeable than they really are. Despite this fact, qualifications and credentials have long served as signals for organizations. As some authors put it, certifications are double-edged, as they can also be used as “credentials” to gain prestige and influence, having nothing to do with competence development, as they are valued as impression management or self-presentation strategies. The data for this exploratory study was gathered from a 58 employee sample of a Portuguese-based multinational software engineering company. An experimental Competence Certification Effects Scale (CCES) was used, and after a consistency analysis, the original 22 items were reduced to 17, grouped in a 4-factor structure: “Certification Intrinsic Value”; “Certification as Training”; “Career Management”; and “Effort Trade-off”. Cronbach`s alphas were .81, .81, .83, and .81, respectively. The study findings indicate that there is a significant difference in the perceived usefulness of a certification, if an employee participates or not in a dedicated certification program. The study further points out that certification programs tend to be judged in an instrumental way, for extrinsic motivation reasons, more by its positive effects in terms of career management or professional within-peers recognition, than by its intrinsic value as institutional learning or knowledge management anchors or personal development drivers.